Letters from Heaven : Popular Religion in Russia and Ukraine - Zayarnyuk, Andriy, 1975-; Himka, John-Paul, 1949- (Book collections on Project MUSE., 2006)
Letters from Heaven features an international group of scholars investigating the place and function of 'popular' religion in Eastern Slavic cultures. The contributors examine popular religious practices in Russia and Ukraine from the middle ages to the present, considering the cultural contexts of death rituals, miracles, sin and virtue, cults of the saints, and icons. The collection not only fills a void in religious scholarship, but also responds to current theoretical challenges. Reflecting critically on the heuristic value of popular religion and on the concept of popular culture in general, Letters from Heaven is characterized by a shift of focus from churches, institutions, and theological discourse to the religious practices themselves and their interconnections with the culture, mentality, and social structures of the societies in question. An important contribution to the fields of religion and Eastern Slavic studies, this volume challenges readers to rethink old pieties and to reconsider the function of religion.